2012
DOI: 10.11648/j.ajns.20120101.11
|View full text |Cite
|
Sign up to set email alerts
|

Oral Contraception and Breast Diseases

Abstract: Abstract:Objective: Benign breast disease includes a wide spectrum of lesions different for histology and natural history, whose association with oral contraceptives is of great interest because there are no univocal results in literature. Subjects and Methods: The purpose of our study is to assess the relationship between women who used long-term estro-progestin (for at least 12 consecutive months up to a maximum of 60 months) and the develop of benign breast disease comparing with a case-control group compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
2
2
0
Order By: Relevance
“…Study of Carbonaro concluded the same as earlier clinical trials, that in women who used hormonal contraceptive preparations there was no development of new benign breast changes nor worsening of preexisting, so the neutral effect was shown. However, there was a mastodynia reduction in patients who used OC for 36 months [35]. In our study, use of progesterone local therapy for 6 months showed no solid benign or malignant thickening, which was in accordance with the above mentioned research.…”
Section: Discussionsupporting
confidence: 91%
“…Study of Carbonaro concluded the same as earlier clinical trials, that in women who used hormonal contraceptive preparations there was no development of new benign breast changes nor worsening of preexisting, so the neutral effect was shown. However, there was a mastodynia reduction in patients who used OC for 36 months [35]. In our study, use of progesterone local therapy for 6 months showed no solid benign or malignant thickening, which was in accordance with the above mentioned research.…”
Section: Discussionsupporting
confidence: 91%
“…This study showed the majority of patients suffering from benign breast tumors do not use oral contraceptives, which is as much as 75.5%. This is in line with Carbonaro (10) that said there is no significant difference between users of oral contraceptives and non-users of oral contraceptives for the incidence of benign breast disease. But this study differs from Sihombing's study (8) which states that oral contraceptives increase the risk of breast tumors and Yu's study (9) in which oral contraceptives increase the risk of fibroadenoma.…”
Section: Discussionsupporting
confidence: 89%
“…Sihombing (8) said that contraceptive pill users have a 3.63 times risk greater for breast tumors compared to noncontraceptive pill users as well as Yu (9) said that oral contraceptive use causes the increased risk for fibroadenoma. While Carbonaro (10) said there is no significant difference between users of oral contraceptives and non-users of oral contraceptives for the incidence of benign breast disease. This is an important situation to study because oral contraception is a method that mostly used by Indonesian women as much as 2,261,480 women in 2013 (11) .…”
Section: Introductionmentioning
confidence: 99%
“…16 In this study, most of the BBL was found in OCP non users which is in contrast with recent study by A. Carbonaro et al who showed no direct relationship between OCP and BBL. 17 Fibroadenoma and fibrocystic disease of breast was more common in nullipara. Other studies showed increased incidence of fibrocystic disease with nulliparity but no relation of nulliparity with fibroadenoma.…”
Section: Discussionmentioning
confidence: 99%